Predatory Mites in Citrus Under Protective Screen - Demard, Emilie; Qureshi, Jawwad (EDIS, 2021)
Managing the Asian citrus psyllid (ACP), a vector of huanglongbing (HLB), is critical for reducing disease incidence and improving tree health. Growing citrus under screened structures, referred to as citrus under protective screen (CUPS), protects trees from ACP and HLB. CUPS provides an opportunity to produce premium-quality fresh fruit by preventing psyllids and HLB from infecting the trees. Peer reviewed through UF/IFAS Citrus Research and Education Center; published in Citrus Industry Magazine.